2007
DOI: 10.1001/archotol.133.8.758
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Results After Stapedotomy With a Nitinol Piston Prosthesis

Abstract: To compare the hearing results in patients with otosclerosis who underwent a stapedotomy with either a platinum wire prosthesis or a commercially available, heat-activated nitinol stapes piston prosthesis. Design: Retrospective medical chart review. Setting: Academic tertiary care medical center. Patients: Seventy-nine consecutive patients diagnosed as having otosclerosis who underwent primary stapedotomy (33 men and 46 women) were included in this study (41 ears per group). Intervention: Stapedotomy. Main Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 26 publications
(31 reference statements)
5
39
1
Order By: Relevance
“…We preferred the 0.6-mm diameter piston, but a successful outcome has also been reported with the application of piston diameters in the range 0.4-0.8 mm [12,13]. Some authors attribute incus necrosis to the extensive application of lasers surrounding the long process of the incus, whereas we agree with those authors who consider this phenomenon to be due to a foreign body reaction [14][15][16]. We previously demonstrated that there was no suspicion of incus necrosis in the mid-term follow-up hearing results in 44 [3].…”
Section: Discussionsupporting
confidence: 66%
“…We preferred the 0.6-mm diameter piston, but a successful outcome has also been reported with the application of piston diameters in the range 0.4-0.8 mm [12,13]. Some authors attribute incus necrosis to the extensive application of lasers surrounding the long process of the incus, whereas we agree with those authors who consider this phenomenon to be due to a foreign body reaction [14][15][16]. We previously demonstrated that there was no suspicion of incus necrosis in the mid-term follow-up hearing results in 44 [3].…”
Section: Discussionsupporting
confidence: 66%
“…For this purpose, a CO 2 , Argon, or KTP laser and bipolar forceps or battery-powered heating units are available. The postoperative hearing results are comparable to those achieved with a conventional prosthesis [20][21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 57%
“…The reason for marginal male preponderance in this study is not known as the disease is known to be predominant in female [1][2][3][4][17][18][19][20][21] . Various fenestration techniques for stapes prosthesis implantation had been described 14,17,[21][22][23] . Sergi et at 22 reported the use of Laser fenestration technique and concluded that laser stapedotomy is an effective and safe procedure for the treatment of otosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery in the form of partial (stapedotomy) or complete (stapedectomy) removal of the fixed stapes and replacement with a prosthetic device (implant) has produced excellent hearing results that remain good for many years and proved to be effective in improving associated tinnitus in the affected patients [14][15][16][17][18] . This surgery that was initially described by Shea 19 had made remarkable advances in both the technique and implant materials which have contributed to improvement in surgical outcome 17,18,20 . The aims of this study were to review all the cases of otosclerosis that were managed by stapedotomy over a year period and evaluate the hearing outcome in the affected patients.…”
Section: Introductionmentioning
confidence: 99%